Assessment of flexural behavior of compressed earth blocks using digital image correlation technique: effect of different types of date palm fibers - Atiki, Elhoussine; Khechai, Abdelhak; Taallah, Bachir; Feia, Sadok; Almeasar, Kamal Saleh; Guettala, Abdelhamid; Canpolat, Orhan (TAYLOR & FRANCIS LTD, 2024)
The present paper provides an experimental investigation to study the effect of the date palm waste fiber (DPW) type and compaction pressure on the flexural behavior of compressed earth blocks (CEBs). The digital image correlation technique (DIC) was used to determine full-field strains of compressed earth blocks. In this context, quicklime as a stabilizer and three different kinds of DPW were added to the CEB composites: Date Palm Waste Aggregate (DPWA), Date Palm Mesh (DPM), and Date Palm Spikelet (DPS). By applying different compacting stresses with static loading, three contents were incorporated into the pressurized mixtures by weight of the waste (0, 0.2, and 0.5%). The results indicate that the flexural strength values were higher for the mixtures with DPWA than those with DPM or DPS. Adding 0.5%DPS increases the ductility of the bricks, resulting in some residual strength and increasing the deflection at failure. As a result of the increase in the compaction pressure, from 2 to 10 MPa, the flexural strength improved by about 262.73 and 371.68% for the control block (samples without DPW) and the block containing 0.5% DPW, respectively. When the compaction pressure increases from 2 to 10 MPa, the apparent modulus of elasticity increases from 393.31 to 809.37 MPa for a block without DPWA and from 214.22 to 321.52 MPa for a block containing 0.5% DPWA. After analyzing the images obtained during the flexural test using the DIC technique, the results of & epsilon;(xx) revealed extremely high localized strains in the center of the block at the bottom of the samples under tension. The strain concentration increases as the fiber content increases. In addition, when the compaction pressures of CEBs are increased, the values of & epsilon;(xx) are increased.
Keywords: Compressed earth blocks; flexural behavior; digital image correlation; date palm waste; modulus of elasticity; MECHANICAL PERFORMANCE; PHYSICAL-PROPERTIES; FRACTURE-BEHAVIOR; BOTTOM ASH; FLY-ASH; CEMENT; CONCRETE; MORTAR; POWDER; WASTE; Engineering